2019
DOI: 10.1021/acsami.9b17820
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance CO2-Selective Hybrid Membranes by Exploiting MOF-Breathing Effects

Abstract: Conventional CO2 separation in the petrochemical industry via cryogenic distillation or aminebased absorber-stripper units is energy intensive and environmentally unfriendly. Membranebased gas separation technology, on the other hand, has contributed significantly to the development of energy-efficient systems for e.g. natural gas purification. The implementation of commercial polymeric membranes in gas separation processes is restricted by their permeabilityselectivity trade-off and by their insufficient ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Nowadays thin film composite (TFC) membranes that consist of a selective, thin polyamide (PA) top layer formed by interfacial polymerization (IP) of amine and acid chloride monomers on a porous substrate are receiving significant attention due to their advantages in different CO 2 separation and capture applications. However, attention still needs to be paid to the well-known trade-off challenge between permeability and selectivity in TFC membranes. , …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays thin film composite (TFC) membranes that consist of a selective, thin polyamide (PA) top layer formed by interfacial polymerization (IP) of amine and acid chloride monomers on a porous substrate are receiving significant attention due to their advantages in different CO 2 separation and capture applications. However, attention still needs to be paid to the well-known trade-off challenge between permeability and selectivity in TFC membranes. , …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Hence, the exploration of new ways to separate air pollutants such as CO 2 and SO 2 is a challenging scientic and technical issue. [5][6][7] The emissions of CO 2 and SO 2 are mainly from the combustion of coal caused by industrial processes and heavy oil used by vehicles, respectively. [8][9][10] Membrane technology as one method for gas separation is promising, and has attracted the attention of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The modular nature of MOFs with aperture size distributions of angstrom-level resolution 7,22,31 is envisioned to allow for high degrees of adsorption selectivity and permselectivity and improved process economics with reduced emissions. Previous studies showed that a mixed-matrix membrane (MMM) composed of a polyimide crosslinker and embedded with NH 2 -MIL-53, a surface-modified variant of an aluminum-based MOF, can be used for separating CH 4 from CO 2 -exhibiting increased CO 2 selectivity without significant loss of its permeability 33 . The improvements were realized in part by the presence of NH 2 groups that aided in regulating the MOF breathing mechanism and penetration of polyimide chains to provide configurational stability 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that a mixed-matrix membrane (MMM) composed of a polyimide crosslinker and embedded with NH 2 -MIL-53, a surface-modified variant of an aluminum-based MOF, can be used for separating CH 4 from CO 2 -exhibiting increased CO 2 selectivity without significant loss of its permeability 33 . The improvements were realized in part by the presence of NH 2 groups that aided in regulating the MOF breathing mechanism and penetration of polyimide chains to provide configurational stability 33 . Complementary, a new humidity-resistant MOF, JNU-2 has shown promise in separation of ethane (C 2 H 6 ) from ethylene (C 2 H 4 ), the single largest feedstock in the petrochemicals industry 22 .…”
Section: Introductionmentioning
confidence: 99%